(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2022)
At the present time, Muslims in Malaysia can apply for a Letter of Administration (LA) at the Small Estate Unit under the Department of Director General of Lands and Mines (JKPTG) when it involves immovable assets only, or immovable and movable assets. However, based on the issue of delay in the administration of the estate, which is becoming increasingly worrying, and the increase of unclaimed money, which is estimated to be up to RM90 billion, the Government of Malaysia has taken a proactive step by amending the Small Estates (Distribution) Act 1955 [Act 98], which has been approved in the Malaysian Parliament on 21 October 2022 and is ready to be implemented soon. Therefore, this study analyzes the implications of the amendment to Act 98, which involves the administration of Muslim estates in Malaysia. The methodology used are document analysis involving the Small Estates (Distribution) (Amendment) Act 2022 (Act A1643) and secondary sources, such as journal articles, proceedings, books, newspaper clippings, and websites. In addition, interviews were also conducted involving agency representatives from Amanah Raya Berhad (ARB) and JKPTG. This study found that there are four main implications to the amendment of Act 98 which involves the expansion of jurisdiction, improving governance, a shorter time period for the administration of the estate, and automatic petitions. Keywords: Small Estates (Distribution) Act 1995 [Act 98], Small Estates (Distribution) (Amendment) Act 2022 [Act A1643], Small Estate, estate administration, Majlis Agama Islam Negeri (MAIN), Amanah Raya Berhad (ARB). Full text: PDF